Assessment of The Success of Regional Autonomy (Regional Expansion) In Terms of Regional Financial Performance in Jambi Regencies - Putra, Agung Rizki; Yanto, Yanto (Fin Sinergy: Jurnal Manajemen Keuangan, 2023)
This research aims to: Analyze the Financial Performance of Expanded Regions and Parent Regions in Regencies/Cities in Jambi Province. Period 2009-2021. The analytical tool used in this research is: to analyze Regional Financial Performance. Research Results on Financial Performance of the expansion regions and parent regions during the research period were classified as non-autonomous. This is because many regions that have been expanded are not yet ready and have not been able to find sources of original regional income, as well as explore the potential of their regions, while the parent regions have lost their original sources of regional income, this is due to the division of original regional sources of income with the expansion areas.